Evaluating public transport accessibility and walkability in Pasig City and their correlation to social and economic characteristics at the barangay level. - Nogueira, Ana Clara Caixeta Szymanski; Diaz, Crispin Emmanuel D.; Lorenzo, Evelyn S.; Montalbo, Cresencio M. Jr. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2022)
Cities worldwide are facing rapid and crescent urbanization. According to the UN Habitat (2020), 56.2% of the global population already lives in urban centers, forecasted to grow by over 60% by 2030. The way cities are planned directly impacts exacerbating or reducing the social disparity. Over the past 55 years, many scholars have discussed how unequal and socially unjust cities are regarding access to land, opportunities, services, and community participation, varying according to gender, age, sexuality, ethnicity, educational level, and economic power.
In Global South nations, social inequalities are influenced directly by uncontrolled 1rbanization and urban and transport planning. The car culture dependency, understood by many developing countries as a condition for their development, resulted in dysfunctional sprawled urban forms (UN Habitat 2013). Those urban forms are characterized by spatial segregation, traffic congestion, and air pollution, resulting in longer commuting times, economic losses, environmental and health problems, and degraded quality of life. This situation is aggravated by policies and investments that favor privately motorized over non-motorized and public transport modes, such as widening/ constructing roads, highways, tunnels, and bridges.
Generally, low-income and vulnerable people tend not to benefit from those projects and are deprived of fully accessing services, opportunities, and leisure activities, which increases, even more, their social exclusion (Maricato 2008). In the Philippines, the situation is no different. The country's national transport policies focus on road infrastructure rather than public transport and non-motorized alternatives, encouraging private car usage (Perez et al. 202 1). Over the past years, the country has faced a rise in private cars fleet, resulting in longer traffic times and increased GHG emissions, followed by economic, environmental, and social deterioration.
Even though the Philippines has established a green agenda with a human-centric approach, of this writing, very few actions were implemented in the transport sector. This situation is aggravated by overlapping functions and lack of communication between the government bodies, and the knowledge gap concerning accurate data on public transportation and other non-motorized modes in the cities. Hence, this research aimed to evaluate the accessibility of public transport and walkability with Pasig City as the case study area. This analysis was expected to help the local administration in future planning by identifying what can be improved to promote a more walkable and connected city for all.
This research mainly used desktop-based data collection, supported by primary interview. Public transportation assessment used GIS applications wherein distance buffers for buses, jeepneys, and utility vehicles ' routes were calculated based on areas subscribed within 400 meters. 400 - 800 meters, and above 800 meters from the services. Final results have shown that 88.39% of the areas were less than 800 meters from the public transport lines. The least serviced ar as were located on the northern and southern fringes of the territory, especially in barangays Santolan, Dela Paz, Manggahan , Rosario, Pinagbuhatan , and San Miguel. Hence, it is suggested that the local administration consider expanding the coverage of public transport services to serve those areas.
Walkability conditions were analyzed based on data collected using image from Google Street View, covering 32.50% of the total roads in the study area. The evaluation parameters were a simplified adaptation of Krambeck's (2006) and Wibowo et al. (2015) studies. Five indicators were used: availability of walking paths, cleanliness, disability infrastructure, obstructions, and amenities. The final walkability scores per barangay revealed that the best walking areas were those in the central and southwestern portions of the city, which are the economic core of Pasig, comprising the Central Business District and the City Hall areas. Furthermore, it was observed that local government needs to invest more in improving the walking infrastructure in all of its urban fabric, given many constraints were perceived that hampered a fluid walking experience, such as presence of barriers, narrow paths, and lack of proper amenities.
Linear regression analyses confirmed a correlation between public transport and walkability scores to some social-economic characteristics. At the barangay level, it was shown that a higher IRA dependency index, presence of informal settlements, a higher share of industrial land uses, higher population, and higher number of senior citizens in the barangays, all correlated with poorer access to public transportation and the lower quality of the walking paths. Hence, these characteristics may be considered by the Pasig City government when planning to improve the local transport system to promote a more just, connected, and livable city.
Thesis
Keywords: Transportation -- Philippines -- Pasig City; Walking -- Philippines -- Pasig City; Choice of transportation -- Philippines -- Pasig City; Urban transportation -- Philippines -- Pasig City